PENGARUH PENAMBAHAN PVA TERHADAP PENGURANGAN RETAK LAPISAN HIDROKSIAPATIT PADA Ti-6Al-4V ELI UNTUK APLIKASI BIOMEDIS - Sanny Ardhy; Islahuddin Islahuddin (Rang Teknik Journal, 2024)
Ti-6Al-4V Extra Low Interstitial (ELI), one of the types of titanium alloys most widely used for orthopedic implants. However, the downside is that titanium is less bioactive. Therefore, Ti-6Al-4V ELI needs to be coated with hydroxyapatite to obtain good osseointegration in the human body. However, the results of several studies show that there are still many cracks found in the surface layer of hydroxyapatite. This research aims to reduce cracks in the Ti-6Al-4V ELI layer. The trick is to add PVA to strengthen the hydroxyapatite layer. This study uses the Dip Coating coating method. The hydroxyapatite used is commercial hydroxyapatite, nano-sized. This hydroxyapatite will later be mixed with Polyvinyl Alcohol (PVA, 17% and 20% by weight). After the specimens were coated, the sintering process was continued at temperatures of 800 0C, 900 0C and 950 0C. Then, microstructure examination was carried out using an optical microscope and Scanning Electron Microscope (SEM). The research results obtained, the addition of PVA can reduce cracks in the coating of the test specimen. Optimal results were obtained by adding PVA (20% weight), at 900 0C T sintering. The surface of the implant material is evenly coated and no cracks are found.